Effect of coal bottom ash as a partial replacement of sand on properties of cement mortar - Norathirah , Radzi (2014)
Coal combustion by-products (CCPs) have been around since man understood that burning coal generates electricity. The concept of sustainable development only reawaken our consciousness to the huge amount of CCPs around us and the need for proper reutilization than the current method of disposal which has severe consequences both to man and the environment. Coal bottom ash (CBA) is formed in coal furnaces. It is made from agglomerated ash particles that are too large to be carried in the flue gases and fail through open grates to an ash hopper at the bottom of the furnace. Bottom ash is mainly comprised of fused coarser ash particles. These particles are quite porous and look like volcanic lava. Bottom ash forms up to 25% of the total ash while the fly ash forms the remaining 75%. One of the most common uses for bottom ash is as structural fill. This thesis presents the result of utilization of waste from thermal power plants to improve some engineering properties of concrete. Effect of coal bottom ash on the properties of cement mortar such as workability, chemical characteristics and pozzolanic activity are presented. Coal bottom ash (CBA) were utilized in partial replacement for fine aggregates and cement respectively in the range 10%, 20% and 30%. Kapar coal bottom ash satisfies the requirement of ACI 213 for fine lightweight aggregate because it has 100% passing the No.4 sieve size (5.tm). The result of compressive strength and degree of hydration shown the 10% replacement has the highest pozzolanic activity due to hydration processed. The workability using bottom ash replacement showed that bottom ash has much higher water absorption ratio as compared to the natural sand since the workability decreased with the increasingly of bottom ash replacement. The XRF testing shown the bottom ash is safely to be used since this material is not harmful and classified as a pozzolanic material. As a conclusion, the presence of bottom ash as sand replacement in cement mortar increased the quantity of water. The weak microstructure obtained with the use of bottom ash is responsible for the decrease in compressive strength.